1984
DOI: 10.4141/cjas84-033
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Lactation Performance of Range Beef and Dairy-Beef Cows

Abstract: An investigation was carried out to study factors influencing milk yields and milk constituents among range cows. June and September measurements of milk yield and constituent percentages of butterfat (BF), protein (PT) and lactose (LT) were taken using 206 and 222 cows in 1976 and 1977, respectively. The cows, representing four beef and dairy-beef breed groups, were from the University of Alberta beef herd and ranged in age from 2 to 10 years. Regression of milk yield on calf age (CA) demonstrated a negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…Although published results vary considerably on the relationship of sex of calf on milk production (Gleddie and Berg 1968;Rutledge etal.l91l;Neville etal.1974;Robison et al 1978;Butson and Berg 1984b) For personal use only. Gleddie and Berg (1968), Butson et al (1980) and Mondragon et al (1983 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although published results vary considerably on the relationship of sex of calf on milk production (Gleddie and Berg 1968;Rutledge etal.l91l;Neville etal.1974;Robison et al 1978;Butson and Berg 1984b) For personal use only. Gleddie and Berg (1968), Butson et al (1980) and Mondragon et al (1983 …”
Section: Methodsmentioning
confidence: 99%
“…Rutledge etal. (1971), Robison et al (1978), and Butson and Berg (1984b) all reported a positive relationship between calf birth weight and milk yield.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…also found differences in milk production among breeds (P < .01), with daily milk for the Hereford being lowest (4.8 kg) and Simmental highest (8.0 kg). Different crosses have been found to produce different amounts of milk at peak lactation Hardt et ai., 1988), to produce different amounts of average daily milk (Daley et aI., 1987;Gaskins and Anderson, 1980;Totusek et aI., 1971;Jeffery et aI., 1971 b;Hardt et aI., 1988;Cobb et aI., 1978b;McGinty and Frerichs, 1971;Todd et aI., 1968;, and to produce different amounts of total milk Butson and Berg, 1984b). There were also breed differences in persistency (Butson and Berg, 1984a).…”
Section: Breed Of Cow and Milk Production Calf Gain And Weaning Weightmentioning
confidence: 99%
“…The effect of birth weight of the calf on milk production of the dam ranged from nonsignificant (Christian et aI., 1965; to moderately positive (Martin and Franke, 1982;Rutledge et aI., 1970a;Robison et aI., 1978;Butson and Berg, 1984b). Larger calves tended to cause their dams to produce more milk because they could consume more (Marston et aI., 1992;Drewry et aI., 1959).…”
Section: Birth Weight and Milk Production Calf Gain And Weaning Weightmentioning
confidence: 99%